Prognostic factors for long-term mortality after surgery of left-sided infective endocarditis - Se Ju Lee; Jung Ho Kim; Yongseop Lee; Sangmin Ahn; Jung Ah Lee; Jinnam Kim; Hyung Jung Oh; Jin Young Ahn; Su Jin Jeong; Jun Yong Choi; Joon-Sup Yeom; Nam Su Ku; et al. (PLoS ONE, 2025)
Background Infective endocarditis has low prevalence but a high mortality rate. Left-sided infective endocarditis (LSIE) has a higher mortality rate than right-sided infective endocarditis. Surgical treatment is occasionally considered for LSIE; however, few data are available on the long-term prognostic factors for LSIE after surgical treatment. This study investigated the risk factors for long-term mortality in LSIE patients who underwent surgical treatment. Methods This retrospective study enrolled adult patients with LSIE who were admitted to Severance Hospital in South Korea and underwent surgical treatment from November 2005 to August 2017. The primary outcome was risk factors for overall all-cause mortality. Multivariable Cox regression analysis was performed to identify risk factors for long-term mortality of patients with LSIE who received surgical treatment. Results This study enrolled 239 with LSIE who underwent surgery. The median follow-up period was 75.9 months, and there were 34 deaths (14.2%) during the study period. Multivariable Cox analysis showed that central nervous system complications (hazard ratio [HR]: 3.55, 95% confidence interval [CI]: 1.76–7.17, P <  0.001), chronic liver disease (CLD) (HR: 4.33, 95% CI: 1.57–11.91, P =  0.005), and age ≥  65 years (HR: 2.65, 95% CI: 1.28–5.51, P =  0.009) were risk factors for overall mortality. Kaplan–Meier analysis indicated a significant difference in survival between patients with and without CNS complications (P <  0.001, log-rank). Conclusion Central nervous system complications, CLD, and older age were associated with long-term mortality in surgically treated patients with LSIE. Preventive strategies for CNS complications would improve the treatment of LSIE.